(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
The final arbiter of consumer acceptance of a food product are sensory studies, which can be roughly categorized into liking studies and quantitative sensory analysis. In the latter sensory qualities of a food product are evaluated by panelists on a defined scale. These are invaluable instruments in setting targets for product development, but also as the final quality arbiters for a new product. Instrumental analysis, be it texture analysis or shear rheology, have served as valuable tools to accelerate food and food ingredient R&D where correlations between instrumental analysis and sensory science can be established. However, there are sensory attributes which are not easily described by shear rheology and other techniques are needed. This is especially true if the kinematic of the deformation at the root of the perception is not matched by shear rheology. This is for example the case with texture length (also called ropiness or stringiness). Despite the relevance of this perception aspect to the quality of the food item, formulation is guided by shear rheology. This bears the risk that formulation recommendations are off target and can lead to costly iterations. We will present a small study which connects careful extensional rheology to a sensory study on a condensed milk model. While the number of samples is small, this study demonstrates the general approach one can take. It points to which attributes are uniquely captured by extensional rheology and therefore where this technique adds distinct value and where conventional shear rheology suffices.